Nomophobia in Nursing Students at Padjadjaran University - Haryati, Evi Annisa; Widianti, Efri; Hidayati, Nur Oktavia (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2020)
ABSTRACT  During the industrial revolution of 4.0, everything becomes easily accessible. One of its developments is information and communication technology. The high use of a smartphone as communication tools can cause dependency which is characterized by repeatedly checking smartphones which can cause addiction so that it can cause fear or phobia, commonly known as Nomophobia. The aim of this study was to determine the overview of nomophobia in Nursing students at Padjadjaran University. This research used a quantitative descriptive method with cross-sectional approach. Samples were taken using a total sampling technique from the population of an active student of the Bachelor program in the year of 2016, 2017, 2018 and 2019 Faculty of Nursing, Padjadjaran University. Data were collected using the Nomophobia Questionnaire (NMP-Q) and analyzed using descriptive frequency distribution. The results of this study showed that the majority of respondents 559 (63.5%) showed moderate nomophobia, as many as 243 respondents (27.6%) showed severe nomophobia and 79 respondents (9%) showed mild nomophobia. The conclusion of this study is that majority of respondents belong to the category of moderate nomophobia. Therefore, it is recommended for the following institution to be able to develop policies that regulate the use of smartphones in the context of clinical education and practice.ABSTRAKPada era revolusi industri 4.0 segala sesuatunya semakin mudah diakses. Salah satu perkembangannya adalah teknologi informasi dan komunikasi. Tingginya penggunaan alat komunikasi smartphone dapat menimbulkan ketergantungan yang ditandai dengan selalu memeriksa smartphone yang dapat menimbulkan suatu kecanduan sehingga dapat menimbulkan ketakutan atau fobia yang lebih dikenal dengan sebutan Nomophobia. Tujuan penelitian ini adalah untuk mengetahui gambaran nomophobia pada mahasiswa Fakultas Keperawatan Universitas Padjadjaran. Penelitian ini menggunakan metode  deskriptif kuantitatif dengan pendekatan cross sectional. Sampel diambil dengan menggunakan teknik total sampling dari populasi mahasiswa aktif program Sarjana angkatan 2016,2017,2018 dan 2019 Fakultas Keperawatan Universitas Padjadjaran. Data dikumpulkan dengan menggunakan instrumen Nomophobia Questionnaire (NMP-Q dan dianalisis secara deskriptif  distribusi frekuensi. Hasil penelitian ini menunjukkan bahwa sebagian besar  responden 559 (63,5%) menunjukkan nomophobia sedang, sebanyak 243 responden (27,6%) menunjukkan nomophobia berat dan sebanyak 79 responden (9%) menunjukkan nomophobia ringan. Simpulan dari penelitian ini adalah sebagian besar responden tergolong kedalam kategori nomophobia sedang. Oleh karena itu, disarankan bagi pihak instansi untuk dapat mengembangkan kebijakan yang mengatur penggunaan smartphone dalam konteks pendidikan dan praktikum klinis.